PENGARUH EKSPEKTASI PERFORMA, EKSPEKTASI USAHA, PENGARUH SOSIAL, DAN KONDISI FASILITAS TERHADAP INTENSI DAN PERILAKU PENGGUNAAN AI DI KALANGAN MAHASISWA: PERAN KEMANDIRIAN BELAJAR SEBAGAI VARIABEL MODERATOR - Isack Josua Sasmita Siahaan; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
In recent years, the development of Artificial Intelligence (AI) technology has progressed rapidly and people have been utilizing it in their daily lives. In Indonesia, the rate of AI has also increased dramatically, particularly among the younger generation. In Indonesia’s higher education setting, the majority of students have also been utilizing AI in their academic activities. This raises the question: why have Indonesian college students been so easily accepting of AI and so keen to adopt it in their studies? Using The Unified Theory of Acceptance and Use of Technology (UTAUT) theoretical framework and the extension of self directed learning as a moderator variable, this research aims to identify the key factors that drive Indonesian college students to accept and use AI on an ongoing basis. 234 verified respondents were analysed using the SEM-PLS method. The results indicated that performance expectancy, social influence, and facilitating conditions are the most significant variables influencing AI use intention and actual behavior. The intention to use AI also significantly influences AI usage behavior. However, effort expectancy was found to have no significant influence on AI use intention and actual behavior. Self-directed learning is also found to have no moderating effect over the UTAUT predictor variables. The findings of this research can serve as a basis for designing proper AI systems and developing regulations to ensure that AI is utilized wisely in Indonesia’s education setting.